USING VIDEOS AS A TEACHING MEDIA FOR READING COMPREHENSION: DOES IT WORK? - Lailatus Sa’adah (Edumedia : Jurnal Keguruan dan Ilmu Pendidikan, 2022)
There are various strategies and techniques of teaching used by teachers to improve students' reading comprehension. The most widely used and challenging tasks for teachers are the implementation of the media. In this study, the researcher employed video of narrative text as a considerable media to enhance students' reading comprehension and as a way to get students attention to study. Moreover, few studies report on the of videos used in teaching learning process in which any result will actually be considered beneficial to the development of teaching. Video of narrative text is a sequence of narrative text which is visualize in form of video. In conducting this study, the researcher used quasi experimental research design. Following the idea, this study was designed to investigate the effect of using video of narrative text on the students' reading comprehension. The tenth-grade students of one of the private schools in Malang were used as the target population of this study. The required data were collected through achievement test. Due to the need to understand the effect, ttest was employed in this present study. The result of this study showed that the use of video of narrative text did not give a significant effect on the students' reading comprehension. It was proven from the calculation result of independent sample ttest. Half of them showed improvement in their but half of them did not. Therefore, there was no significant different between students who taught by using video of narrative text and original text.